2021
DOI: 10.1109/access.2021.3063123
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Short-Term Load Forecasting Model Based on Improved Fuzzy C-Means Clustering, Random Forest and Deep Neural Networks

Abstract: Short-term load forecasting (STLF) plays an important role in the secure and reliable operation of the electric power system. Grouping similar load profiles by a clustering algorithm is a common method to reduce the uncertainty of electric consumption data. However, due to the uneven distribution of different date types in a historical data set, the tradition fuzzy c-means clustering (FCM) algorithm cannot identify typical load consumption patterns accurately. To solve this problem, a novel STLF model based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The best architectural modeling value is determined by calculating the Maximum Absolute Percentage Error (MaxAPE) value from each test and accumulated by the average value approach. Forecasting is done using limited training data, namely four days or 4 x 48 data, to predict the next one day or 1 x 48 data, which is sufficient according to the author's previous research [6], [25] The results of the LSTM architectural modeling test are presented in Table 2. on these results, it was found that the best LSTM architecture model lies in model number 9, with the smallest MaxAPE average value of 7,061.…”
Section: Conventional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best architectural modeling value is determined by calculating the Maximum Absolute Percentage Error (MaxAPE) value from each test and accumulated by the average value approach. Forecasting is done using limited training data, namely four days or 4 x 48 data, to predict the next one day or 1 x 48 data, which is sufficient according to the author's previous research [6], [25] The results of the LSTM architectural modeling test are presented in Table 2. on these results, it was found that the best LSTM architecture model lies in model number 9, with the smallest MaxAPE average value of 7,061.…”
Section: Conventional Methodsmentioning
confidence: 99%
“…In general, this method is used to predict Sequential Values or forecasting. This method is applied in many fields such as cellular network [16], power generation [24], bearing conditions [15], Load Forecasting [6], [25], etc. LSTM was developed to solve the RNN problem [26], namely the loss of important information at the beginning of knowledge; if the sequence processed is long enough (forward propagation) and the gradient vanishing problem (backward propagation), the gradient value is very small, so it does not contribute to changes in weight.…”
Section: Forecasting Modellingmentioning
confidence: 99%
“…In the same category, the load growth rate of known years is used as the load growth rate of predicted years, so as to realize load forecasting. Fuzzy cluster analysis method can consider many related factors at the same time, which is consistent with the characteristics of policy influencing many related factors [32]. However, fuzzy clustering cannot carry quantification weights, and the influence of different factors on load is not considered, so it is improved to weighted fuzzy clustering on the basis of fuzzy clustering.…”
Section: Medium and Long-term Load Forecasting Based On Weighted Fuzzy Cluster Analysismentioning
confidence: 97%
“…Accurate short-term load forecasting results can be used to form a more reasonable home energy scheduling plan [7][8][9]. Since dispatching management is only applied in the large-scale regions in the traditional power grid, existing electric load forecasting methods are mainly used to obtain regional power load for generation scheduling, transaction scheduling, and network dispatching [10,11]. These load forecasting methods can be mainly grouped into three categories, including similar day or similar time interval-based forecasting methods, frequency component-based forecasting methods, and meteorological factor-based load forecasting methods.…”
Section: Introductionmentioning
confidence: 99%